Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. - Matías, Luis; Zamora, Regino; Castro, Jorge (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.
Keywords: Angiosperms; Angiosperms: growth & development; climate change; Droughts; Ecosystem; Mediterranean Region; Rain; rainfall variability; Recruitment; Seedling; Seedling: growth & development; Spain; summer drought; Vegetation dynamics

Seasonal and inter-annual variations of gas exchange in thirteen woody species along a climatic gradient in the Mediterranean island of Mallorca - Gulías, J.; Cifre, J.; Jonasson, S.; Medrano, H.; Flexas, J. (Flora - Morphology, Distribution, Functional Ecology of Plants, 2009)
We studied the inﬂuence of summer drought and winter temperatures on seasonal and spatial variations of lightsaturated net photosynthesis and stomatal conductance in Mediterranean woody species. We measured variations in leaf gas exchange over 3 years in 13 Mediterranean trees and shrubs, located at four different sites along a climate gradient of temperature and precipitation in the island of Mallorca (West Mediterranean basin). Net photosynthesis and stomatal conductance were at a maximum during spring, autumn or winter and at a minimum during summer in most sites, species and years. Nevertheless, important spatial, temporal and species-speciﬁc variations were observed. Summer drought limitation to gas exchange was greatest in the dry part of the transect, where many species showed their maximum gas exchange rate during winter. In contrast, winter temperatures limited gas exchange of many species at the wet and cool end of the transect, while summer depression of gas exchange was shorter and less pronounced. These results suggest that the effect on carbon ﬁxation and productivity by the predicted future increase of aridity in the Mediterranean basin will depend on whether gas exchange is mostly limited by summer drought or by low winter temperatures.
Keywords: evergreen sclerophyllous species; Mediterranean shrubs; Mediterranean trees; photosynthesis; summer drought

Oak seedling survival and growth along resource gradients in Mediterranean forests: implications for regeneration in current and future environmental scenarios - Gómez-Aparicio, L.; PÉREZ-RAMOS, I. M.; Mendoza, I.; Matías, L.; Quero, J. L.; Castro, J.; Zamora, R.; MARAÑON, T. (Oikos, 2008)
Understanding seedling performance across resource gradients is crucial for defining the regeneration niche of plant species under current environmental conditions and for predicting potential changes under a global change scenario. A 2-year field experiment was conducted to determine how seedling survival and growth of two evergreen and two deciduous Quercus species vary along gradients of light and soil properties in two Mediterranean forests with contrasting soils and climatic conditions. Half the seedlings were subjected to an irrigation treatment during the first year to quantify the effects on performance of an alteration in the summer drought intensity. Linear and non-linear models were parameterized and compared to identify major resources controlling seedling performance. We found both site-specific and general patterns of regeneration. Strong site-specificity was found in the identity of the best predictors of seedling survival: survival decreased linearly with increasing light (i.e. increasing desiccation risk) in the drier site, whereas it decreased logistically with increasing spring soil water content (i.e. increasing waterlogging risk) in the wetter site. We found strong empirical support for multiple resource limitation at the drier site, the response to light being modulated by the availability of soil resources (water and P). Evidence for regeneration niche partitioning among Quercus species was only found at the wetter site. However, at both sites Quercus species shared the same response to summer drought alleviation through water addition: increased first-year survival but not final survival (i.e. after two years). This suggests that extremely dry summers (i.e. the second summer in the experiment) can cancel out the positive effects of previous wetter summers. Therefore, an increase in the intensity and frequency of summer drought with climate change might cause a double negative impact on Quercus regeneration, due to a general reduction in survival probability and the annulment of the positive effects of (infrequent) ‘wet’ years. Overall, results presented in this study are a major step towards the development of a mechanistic model of Mediterranean forest dynamics that incorporates the idiosyncrasies and generalities of tree regeneration in these systems, and that allow simulation and prediction of the ecological consequences of resource level alterations due to global change.
Keywords: abiotic factors; growth (voyant); light; Mediterranean forests; Quercus; Regeneration; seedling survival; soil conditions; summer drought

Photosynthesis and photoprotective strategies in Laurus nobilis L. and Quercus ilex L. under summer drought and winter cold - Arena, C.; Vitale, L.; Virzo De Santo, A. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2008)
Abstract Photosynthesis and photoprotective mechanisms were investigated in the field on Laurus nobilis L. and Quercus ilex L. leaves exposed to summer drought (July) and winter cold (February) conditions compared with no-stress conditions (May). In July, net photosynthetic rate (A) and stomatal conductance (g s) decreased significantly compared with May in both species; conversely the highest ETR/A ratio and no difference in non-photochemical quenching (NPQ) was observed. In February A, g s and ETR/A declined compared with May but the highest NPQ were found in both species. Our data suggest that during summer, an increase of photochemical alternative pathways to carbon reduction, were able to effectively protect the photosynthetic apparatus under drought. In winter, the thermal dissipation of excess absorbed light constitutes the main safety valve for the photosynthetic apparatus.
doi: 10.1080/11263500802410819doi: 10.1080/11263500802410819The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Dissipative processes; L. nobilis; leaf gas-exchange; Q. ilex; summer drought; winter cold

Photosynthesis and photoprotective strategies in Laurus nobilis L. and Quercus ilex L. under summer drought and winter cold - Arena, C; Vitale, L; Virzo de Santo, A (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2008)
Abstract Photosynthesis and photoprotective mechanisms were investigated in the field on Laurus nobilis L. and Quercus ilex L. leaves exposed to summer drought (July) and winter cold (February) conditions compared with no-stress conditions (May). In July, net photosynthetic rate (A) and stomatal conductance (g s) decreased significantly compared with May in both species; conversely the highest ETR/A ratio and no difference in non-photochemical quenching (NPQ) was observed. In February A, g s and ETR/A declined compared with May but the highest NPQ were found in both species. Our data suggest that during summer, an increase of photochemical alternative pathways to carbon reduction, were able to effectively protect the photosynthetic apparatus under drought. In winter, the thermal dissipation of excess absorbed light constitutes the main safety valve for the photosynthetic apparatus.
doi: 10.1080/11263500802410819
Keywords: Dissipative processes; L. nobilis; leaf gas-exchange; Q. ilex; summer drought; winter cold

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - LO GULLO, M A; Salleo, S (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - Lo Gullo, M. A.; Salleo, S. (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism